2010
DOI: 10.1158/1538-7445.am10-5435
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5435: A novel HDAC inhibitor, CKD-581, demonstrates a potent in vivo efficacy in various human tumor xenograft models

Abstract: Histone deacetylases (HDAC) inhibition is now well established as a new approach for solid and hematological tumor therapy. Studies with different HDAC inhibitors showed broad activity toward cancer cells, i.e. activation of proapoptotic pathway and inhibition of antiapoptotic pathway, induction of cell differentiation, antiangiogenic activity and synergism with other cancer therapeutics. Several HDAC inhibitors have demonstrated therapeutic benefits and are under clinical investigations as mono- or combi-ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In preclinical in vitro and in vivo studies, CKD-5 has demonstrated strong anti-tumor effects against multiple myeloma and cutaneous T-cell lymphoma [ 16 , 17 ]. CKD-5 has also shown considerable cytotoxicity in multiple solid tumor cell lines and xenograft mouse models of colon, prostate, and lung cancer [ 18 ]. A phase I study of CKD-5 recently reported promising results with minimal side effects and modest anti-tumor efficacy in patients with lymphoma or multiple myeloma refractory to standard therapy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical in vitro and in vivo studies, CKD-5 has demonstrated strong anti-tumor effects against multiple myeloma and cutaneous T-cell lymphoma [ 16 , 17 ]. CKD-5 has also shown considerable cytotoxicity in multiple solid tumor cell lines and xenograft mouse models of colon, prostate, and lung cancer [ 18 ]. A phase I study of CKD-5 recently reported promising results with minimal side effects and modest anti-tumor efficacy in patients with lymphoma or multiple myeloma refractory to standard therapy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%